Penerapan Metode Perbandingan Eksponensial Pada Penilaian Proses Belajar Mengajar di Fakultas Teknik Universitas Muhammadiyah Bengkulu - ujang juhardi; Rozali Toyib; Agusdi Syafrizal (Universitas PGRI Semarang, 2019)
Problems that often occur in the field of education are the teaching and learning process of lecturers to students, the assessment of the teaching and learning process of lecturers is still number two or eliminated and the assessment through eye screen, without having to be given a special assessment of the concerned. This actually creates a problem, namely, it cannot be known how the progress of teaching and learning process of lecturers towards students. The Exponential Comparison method can reduce the bias that might occur in the analysis, because the resulting score illustrates the order of priorities that becomes large so that the priority order of alternative decisions becomes more apparent. Test Results Based on the results of tests that have been done, found the results of 6 (six) Very Good Lecturers, 11 (eleven) Good Lecturers, and 2 (two) Sufficient Lecturers, If the value entered on each criterion exceeds the range of scores has been determined, then the value is automatically returned empty, and must fill the value with a range of values.